Health, subjective financial situation and well-being: a longitudinal observational study - Paul Downward; Simona Rasciute; Harish Kumar (Health and Quality of Life Outcomes, 2020)
Abstract Background An individual’s financial situation is a key contributor to their overall well-being. Existing research has examined the direct economic consequences of changes in health upon out-of-pocket healthcare expenditure, participation in the labour force and potential earnings. There is also research exploring an individual’s concern about their subjective financial situation regardless of the level of their income or work status on their health. In contrast, this paper conducts a causal analysis of the effects of general and mental health on an individual’s subjective evaluation of their financial situation controlling for their work status and income. This is of importance because current health policy in the United Kingdom (UK) stresses the role of health as an asset which can mediate the wider flourishing of individuals. Moreover, subjective financial situation comprises a key component of well-being now being measured and sought in social welfare policy. Methods Fixed effects instrumental variable panel data regression analysis is applied to 25 years of longitudinal data, from 1991, drawn from the harmonised British Household Panel Survey (BHPS) and Understanding Society Survey (USS). Results Improved general health and reduced mental illness both improve the subjective financial situation of males and females. However, these affects diminish across older cohorts of males and females. Conclusions Investing in and improving general and mental health can improve the subjective financial situation and hence well-being of individuals. The targeting of health also needs to take account of an individuals’ life-stage.